Optimal dimension design of high-temperature superconducting levitation weft insertion guideway - Zhang Chengjun; Li Chengyuan; Liu Pengwei; Wang Yi; Zuo Xiaoyan; Zhang Chi; Xu Chuqiao (AUTEX Research Journal, 2025)
To address the issues of friction, heat generation, and noise associated with traditional shuttle systems during flight, this article proposes a high-temperature superconducting (HTS) shuttle that stably levitates above a Halbach permanent magnet guideway (PMG) without energy consumption. The levitation force experienced by the superconductor is closely related to the dimensions of both the PMG and the superconductor. To ensure the stability of the shuttle’s levitation during the weaving process, an optimization method that considers both the levitation force and material usage is proposed. The ratio of the levitation force per unit length of the superconductor (F Z) to the PMG’s height (h pm) is defined as F h, with the optimal height of the PMG occurring when F h is maximized. Based on this, simulations were conducted to analyze the trend of levitation force changes with variations in guideway’s width, height, and superconductor material’s thickness. Finally, an experimental platform was built to verify the accuracy of the simulation results. The findings indicate that rational optimization of guideway dimensions can enhance the system’s levitation performance while optimizing material usage, with the optimized guideway providing significantly enhanced levitation force. This study offers theoretical and practical guidance for the design and application of HTS levitation guideways.